2010
DOI: 10.1007/s00787-010-0090-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of attention-deficit/hyperactivity disorder: an overview

Abstract: As heritability is high in attention-deficit/hyperactivity disorder (ADHD), genetic factors must play a significant role in the development and course of this disorder. In recent years a large number of studies on different candidate genes for ADHD have been published, most have focused on genes involved in the dopaminergic neurotransmission system, such as DRD4, DRD5, DAT1/SLC6A3, DBH, DDC. Genes associated with the noradrenergic (such as NET1/SLC6A2, ADRA2A, ADRA2C) and serotonergic systems (such as 5-HTT/SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
159
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(168 citation statements)
references
References 192 publications
(306 reference statements)
2
159
0
7
Order By: Relevance
“…At its core is a persistent and pervasive pattern of inattention, overactivity and impulsiveness (1,2). ADHD often overlaps with other disorders (e.g., conduct disorder, anxiety, dyslexia; (3,4,5) and is associated with significant impairment across functional domains and in quality of life (e.g., home, school, work) (6).…”
mentioning
confidence: 99%
“…At its core is a persistent and pervasive pattern of inattention, overactivity and impulsiveness (1,2). ADHD often overlaps with other disorders (e.g., conduct disorder, anxiety, dyslexia; (3,4,5) and is associated with significant impairment across functional domains and in quality of life (e.g., home, school, work) (6).…”
mentioning
confidence: 99%
“…Literatürde DEHB'nin kalıtsal aktarılabi-lirliğine ilişkin çalışmalar vardır. [43][44][45] DEHB'li çocukların anne-babalarında erişkin DEHB yaygınlığının ve belirtilerinin arttığı bildirilmiştir. 46,47 Anne-babaların psikiyatrik tanılarını değerlendir-mek için yapılandırılmış bir klinik görüşme tekniği uygulanmamış olması, anne-babalarda şimdiki DEHB belirtilerini değerlendirmek amacıyla bir Anatolian Journal of Psychiatry 2018; 19(4):411-418 ölçeğin kullanılmamış olması, anne-babanın ayrı ayrı değerlendirilmemiş olması, depresyonu yordayabilecek farklı değişkenlerin değerlendiril-memiş olması, aleksitiminin klinik bir görüşmede ele alınmamış olması bu çalışmanın sınırlılık-larını oluşturmaktadır.…”
Section: çOcuk Ve Ergenlerde Davranış Bozuklukları Için Dsm-iv'e Dayaunclassified
“…However, we believe that thoughtful, hypothesis-driven studies are valuable as long as the researchers are cognizant of potential replication problems. Notably, a large number of studies have found that the DRD4 gene, which encodes proteins that respond to the neurotransmitter dopamine in the brain, is related to a number of externalizing types of behaviors, such as novelty seeking, aggression, and hyperactivity (Banaschewski, Becker, Scherag, Franke, and Coghill 2010;Farbiash, Berger, Atzaba-Poria, and Auerbach 2014;Ray et al 2009). Similarly, other genes have been identified repeatedly across different studies, suggesting that they code for neurotransmitter action in the brain that is related to certain behaviors.…”
Section: Molecular Genetic Studiesmentioning
confidence: 99%